2022
DOI: 10.1021/acs.bioconjchem.2c00506
|View full text |Cite
|
Sign up to set email alerts
|

Large Protein Assemblies for High-Relaxivity Contrast Agents: The Case of Gadolinium-Labeled Asparaginase

Abstract: Biologics are emerging as the most important class of drugs and are used to treat a large variety of pathologies. Most of biologics are proteins administered in large amounts, either by intramuscular injection or by intravenous infusion. Asparaginase is a large tetrameric protein assembly, currently used against acute lymphoblastic leukemia. Here, a gadolinium(III)-DOTA derivative has been conjugated to asparaginase, and its relaxation properties have been investigated to assess its efficiency as a possible th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…A substantial decrease in rotation can be achieved by using molecules with a higher molecular weight and size. Recent studies have demonstrated that linking contrast agents to large molecules and assemblies (i.e., dextran [ 20 ], dendrimers [ 21 , 22 , 23 ], liposomes [ 24 , 25 , 26 ], nanoparticles [ 27 , 28 ], fullerenes [ 29 ], micelles [ 30 , 31 ], peptides [ 32 , 33 , 34 ] and proteins [ 35 , 36 , 37 ]) can substantially increase T1 relaxivity. In addition, the integration of Gd(III) ions within various macromolecules can lead to the formation of multiple paramagnetic centers, thereby conferring enhanced sensitivity [ 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…A substantial decrease in rotation can be achieved by using molecules with a higher molecular weight and size. Recent studies have demonstrated that linking contrast agents to large molecules and assemblies (i.e., dextran [ 20 ], dendrimers [ 21 , 22 , 23 ], liposomes [ 24 , 25 , 26 ], nanoparticles [ 27 , 28 ], fullerenes [ 29 ], micelles [ 30 , 31 ], peptides [ 32 , 33 , 34 ] and proteins [ 35 , 36 , 37 ]) can substantially increase T1 relaxivity. In addition, the integration of Gd(III) ions within various macromolecules can lead to the formation of multiple paramagnetic centers, thereby conferring enhanced sensitivity [ 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their efficiency is first of all represented by their relaxivity (r 1 ), i.e., the relaxation enhancement brought to solvent water protons at a concentration of 1 mM. 8,9 Over the years, probe developers have paid great attention to improving the relaxivity of gadolinium-based contrast agents (GBCAs), 10,11 in particular, by optimizing their structures in terms of the number and exchange rate of the coordinated water molecules in the inner and in the second coordination sphere 12−14 and by controlling the molecular reorientational time through the introduction of substituents on the surface of the ligand capable of either increasing their molecular weight (MW) 15 or setting up suitable interactions with macromolecules. 10,16−18 Often, the target macromolecule is represented by human serum albumin (HSA) 19,20 thus endowing the GBCA with blood pool properties, with a primary aim of application in the field of the acquisition of angiographic images.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Contrast agents (CAs) play a crucial role in diagnostic magnetic resonance imaging (MRI) as they add relevant physiological information to the outstanding anatomical resolution of the images acquired with this modality. They usually consist of paramagnetic gadolinium complexes that cause a marked reduction in the proton relaxation times in the regions where they distribute. Their efficiency is first of all represented by their relaxivity ( r 1 ), i.e., the relaxation enhancement brought to solvent water protons at a concentration of 1 mM. , Over the years, probe developers have paid great attention to improving the relaxivity of gadolinium-based contrast agents (GBCAs), , in particular, by optimizing their structures in terms of the number and exchange rate of the coordinated water molecules in the inner and in the second coordination sphere and by controlling the molecular reorientational time through the introduction of substituents on the surface of the ligand capable of either increasing their molecular weight (MW) or setting up suitable interactions with macromolecules. , Often, the target macromolecule is represented by human serum albumin (HSA) , thus endowing the GBCA with blood pool properties, with a primary aim of application in the field of the acquisition of angiographic images. In most cases, the binding to HSA has been pursued through the introduction of substituents capable of recognizinng the well-known binding sites for lipophilic drugs usually identified as the Sudlow sites. , …”
Section: Introductionmentioning
confidence: 99%